KEABSAHAN INFORMED CONSENT SEBAGAI ALAT BUKTI DALAM PERSIDANGAN TINDAK PIDANA KESEHATAN - Ni Wayan Diah Sukmadewi; I Made Wirya Darma; I Nyoman Budiana; Putu Eva Ditayani Antari (The Juris, 2025)
In health crimes, informed consent is often presented as evidence in court. However, the validity of informed consent is often debated, because informed consent is evaluated based on formal aspects, namely the existence of a document signed by the patient or their family. Technically, this is considered sufficient to prove consent to medical treatment. The purpose of this study is to examine and analyze the validity of informed consent as evidence in medical malpractice trials. The research method adopted in this study is normative legal research through a legislative approach, applying Law Number 17 of 2023 concerning Health and the Criminal Procedure Code. This study uses a descriptive analysis technique. The results show that informed consent can be classified as documentary evidence and circumstantial evidence in court. As documentary evidence, informed consent takes the form of a written document containing a signature. On the other hand, as circumstantial evidence, informed consent refers to its relevance to witness testimony and expert testimony related to the criminal act that occurred. Therefore, the validity of informed consent is evaluated not only from a formal aspect but also from a substantive aspect.